DETERMINATION OF WATER-SOLUBLE VITAMINS B1, B2, B3, B6, B9, B12 AND C ON C18 COLUMN WITH PARTICLE SIZE 3 µM IN SOME MANUFACTURED FOOD PRODUCTS BY HPLC WITH UV-DAD/FLD DETECTION - Antakli, Saad; Sarkees, Nazeera; Sarraf, Tereza (International Journal of Pharmacy and Pharmaceutical Sciences, 2015)
Objective: Objective of the study was to develop a simple, precise and accurate RP-HPLC ion-pair method, for the determination of water-soluble vitamins (B1, B2, B3, B6, B9, B12, and C) in some manufactured food products. Methods: RP-HPLC with C18 BDS (100 x 4.6 mm; 3 µm) column were used. Mobile phase constituents were solvent (A): 5.84 mM of hexane-1-sulfonic acid sodium: acetonitrile (95:5) with 0.1% triethylamine at pH 2.5 and solvent (B): 5.84 mM of hexane-1-sulfonic acid sodium: acetonitrile (50:50) with 0.1% triethylamine at pH 2.5, flow rate 1.6 ml/min, at column temperature 40 °C and suitable detection wavelength. Results: Two different detectors were used: photo diode array detector (UV-DAD) and the fluorescence detector (FLD). Calibration graphs plotted with five concentrations of each vitamin where linear regression coefficients R2˃ 0.9972. LOQ values were 50.0, 81.0, 19.1, 19.0, 30.0, 9.7, 50.0 µg/l with DAD for vitamins B1, B2, B3, B6, B9, B12 and C respectively, and 5.7, 4.1 µg/l with FLD for vitamins B2, B6 respectively. LOD values were 16.5, 26.7, 6.3, 6.3, 9.9, 3.2, 16.5 µg/l with DAD for vitamins B1, B2, B3, B6, B9, B12 and C respectively, and 1.9, 1.3 µg/l with FLD for vitamins B2, B6 respectively. Conclusion: The proposed method was successfully applied to analysis mixture of seven water-soluble vitamins in pure form and in manufactured food products, with average recovery of 98.14% to 100.96%.